Analysis of the perspectives of pension assets investing . (Journal of Economic Research & Business Administration, 2015)
Investment process in which means of the pension fund participate, hould be considered as the process of attracting of owner of pension funds (investors), to the object of investment (economic subject) with the aim of achieving effective development of social economic system, in the frame of which they interact. In the article the author analyses the point of investing pension assets (further Project) of Savings Pension Fund (SPF) with the help of one of the main instruments of regular strategic management, SWOT-analysis. During the analysis weaknesses and strengths of the project were revealed, as well as potential opportunities and threats. As the result the directions of Fund development were elaborated and the ways of distribution of assets according to segment were defi ned. Strong and weak sides of the investment Project are its intersystem compounds. They are under control and correction of the owner of the Project (in this case states and FPS). The source of the possibilities and threats are external environment of the Project that is why they may not be corrected internally in the project. Vice Versa: Project will be successful if it is adapted in the best way to the potential threats and possibilities of the external world.
Keywords: assets of pension fund; managing assets of pension fund; investments; fi nancial instruments; risks; profi tability; SWOT-analysis; strengths; weaknesses; opportunities and threats